2019
DOI: 10.4022/jafib.2148
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Left Atrial Function in Patients with Paroxysmal, Persistent, and Permanent Atrial Fibrillation Using Two-Dimensional Strain.

Abstract: Background and purpose: Atrial fibrillation (AF) has a progressive nature, leading to structural, functional, and electrical changes in the left atrium (LA). Enhanced response to treatment in patients with AF can be achieved through improved knowledge of atrial structure and a better understanding of its function. The aim of this study was to assess LA strain and its determinants in patients with paroxysmal (PAF), persistent (PsAF), and permanent AF (PmAF). Methods: Fifty-eight patients with registered non-val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…A plausible explanation for the lower LAEF in patients with a prior AF history is a slower reverse remodeling which may be secondary to irreversible structural remodeling after their previous episodes of AF. These findings are consistent with another study reporting lower LAEF in patients with persistent or permanent AF as compared with paroxysmal AF and increased LAVI with the severity of AF type [21]. Moreover, LAEF seems to be significantly lower in persistent AF patients with arrhythmia recurrences after LA ablation versus those without, indicating that more extensive irreversible remodeling is an arrhythmia precursor [22].…”
Section: Discussionsupporting
confidence: 91%
“…A plausible explanation for the lower LAEF in patients with a prior AF history is a slower reverse remodeling which may be secondary to irreversible structural remodeling after their previous episodes of AF. These findings are consistent with another study reporting lower LAEF in patients with persistent or permanent AF as compared with paroxysmal AF and increased LAVI with the severity of AF type [21]. Moreover, LAEF seems to be significantly lower in persistent AF patients with arrhythmia recurrences after LA ablation versus those without, indicating that more extensive irreversible remodeling is an arrhythmia precursor [22].…”
Section: Discussionsupporting
confidence: 91%
“…Patients with unstable coronary artery disease (CAD), exacerbation of chronic heart failure, uncontrolled hypertension, recent (<3 months) thromboembolic events such as stroke/TIA or systemic embolism, neoplastic disease, connective tissue disease, uncontrolled thyroid disease and chronic kidney disease (CKD) stage 4 or higher, with an active infection or undergoing treatment with steroids were excluded from the study. 15 …”
Section: Methodsmentioning
confidence: 99%
“… 16 A standardized questionnaire was used to collect the patients’ demographics data, as well as information about their cardiovascular risk factors and current treatment. 15 The CHA 2 DS 2 -VASc score was used to evaluate their risk of stroke or systemic embolism. 17 We estimated the patients’ bleeding risk using the HAS-BLED score.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, quantification of LA longitudinal strain and strain rate have also been validated using CMR feature tracking from cine CMR images 81 . In patients with AF, lower LA strain has been linked to a higher burden of LA fibrosis 82,83 with regional LA strain significantly lower in LA areas with LGE observed on CMR, indicating areas of LA fibrosis compared to LA areas without LGE 84 while another retrospective study looking at n = 971 AF patients enrolled in the ENGAGE AF‐TIMI 48 trial, showed progressive reduction in LA emptying fraction and increase in LA volume index as AF subtype progresses from paroxysmal, to persistent and permanent, respectively. However, there are some limitations to the use of echo‐derived LA strain and strain rate as a fibrosis surrogate, and these include:…”
Section: Identification Of Atrial Fibrosismentioning
confidence: 99%